2006
DOI: 10.1155/2006/921694
|View full text |Cite
|
Sign up to set email alerts
|

BsmI, TaqI, ApaI and FokI Polymorphisms in the Vitamin D Receptor (VDR) Gene and the Risk of Osteoporosis: A Meta‐Analysis

Abstract: A meta-analysis regarding BsmI, TaqI, ApaI and FokI polymorphisms in the vitamin D receptor (VDR) gene and their associations with osteoporosis in females is reported. The meta-analysis involved 14, seven, seven and three studies for BsmI, TaqI, ApaI and FokI polymorphisms, respectively. The studies were association studies with osteoporotic cases and controls free of osteoporosis that provided the genotype distribution of individual cases and controls. For the BsmI polymorphism, the allele contrast b vs. B sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 42 publications
(83 reference statements)
5
71
1
7
Order By: Relevance
“…[28,29] All our HCV-4 patients had suboptimal vitamin D levels with the majority being severely deficient (86%). Possible explanations for the association of HCV with vitamin D deficiency have included decreased 25-alpha hydroxylation in the liver, HCV may have the ability to directly suppress 25-alpha hydroxylation through inducing cytokines and oxidative stresses, and a recent study has shown that HCV alters lipid metabolism directly reducing production of 7-dehydrocholesterol, the precursor of endogenouslyproduced vitamin D. [30,31] The independent effect of HCV on vitamin D levels is strongly supported by our finding of the remarkable improvement in vitamin D levels after successful eradication of HCV and its persistence in non-responders.…”
Section: Discussionmentioning
confidence: 98%
“…[28,29] All our HCV-4 patients had suboptimal vitamin D levels with the majority being severely deficient (86%). Possible explanations for the association of HCV with vitamin D deficiency have included decreased 25-alpha hydroxylation in the liver, HCV may have the ability to directly suppress 25-alpha hydroxylation through inducing cytokines and oxidative stresses, and a recent study has shown that HCV alters lipid metabolism directly reducing production of 7-dehydrocholesterol, the precursor of endogenouslyproduced vitamin D. [30,31] The independent effect of HCV on vitamin D levels is strongly supported by our finding of the remarkable improvement in vitamin D levels after successful eradication of HCV and its persistence in non-responders.…”
Section: Discussionmentioning
confidence: 98%
“…In the GENOMOS study, no association of BsmI-ApaI-TaqI(VDR) haplotype with any osteoporotic phenotype was found, whereas Cdx2(VDR) was associated with risk of vertebral fracture (Uitterlinden et al 2006). In FokI(VDR), no association with BMD has been found (Uitterlinden et al 2006, Zintzaras et al 2006.…”
Section: Discussionmentioning
confidence: 98%
“…The VDR gene is one of the most widely studied osteoporosis-related genes and numerous genetic association studies have yielded conflicting results (Thakkinstian et al 2004, Fang et al 2005, Zintzaras et al 2006. For BsmI(VDR), the metaanalysis has shown contradictory results in BMD-fn (Cooper & Umbach 1996, Gong et al 1999, Thakkinstian et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis consisted of the main (overall) analysis, which includes all available data, subgroup analyses by ''race,'' and sensitivity analysis, which examines the effect of excluding specific studies Zintzaras et al 2006d). The distribution of the genotypes in the control group was tested for HardyWeinberg equilibrium (HWE) using an exact test (Weir 1996).…”
Section: Meta-analysismentioning
confidence: 99%